Understanding Complex Electrochemical Impedance Spectroscopy in Corrosion Systems Using in-situ Synchrotron Radiation Grazing Incidence X-ray Diffraction - Alam, M.; Wai Lyn Chan, E.; De Marco, Roland; Huang, Y.; Bailey, S. (Wiley - VCH Verlag GmbH & Co. KGaA, 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, WeinheimThe difficulty in interpreting electrochemical impedance spectroscopy (EIS) data has limited the potential of the method despite its utility as an electrochemical method for studies of electrode reactions and interfacial structures. Taking the test case of the carbon dioxide corrosion of carbon steel, in-situ synchrotron radiation grazing incidence X-ray diffraction (SR-GIXRD) has been demonstrated to be a powerful technique for validating and understanding the interfacial structures associated with complex EIS data. Carbon dioxide corrosion was found to occur in several steps, which may only be surmised by EIS, but the use of SR-GIXRD in conjunction with EIS has enabled the establishment of a link between EIS time constants and structural changes associated with the evolution of corrosion products with time. By comparison to previous studies by the authors and others in this field, this communication provides the first direct experimental evidence linking SR-GIXRD surface compositional data to otherwise indistinctive EIS time constants.